Most likely to die - Jackson, Lisa.; Staub, Wendy Corsi; Barton, Beverly; Copyright Paperback Collection (Library of Congress) (New York : Kensington Pub., 2007)
It's been 20 years since the night Jake Marcott was brutally murdered at St. Elizabeth High School in Portland, Oregon. It is a night that shattered the lives of three women. A class reunion has been scheduled, and a killer will finish what was started long ago.
Includes excerpts from Dying game: p. [475]-479.
Keywords: High schools; Revenge